Investigating herbivory and plant origin on tall-statured grasses in South Africa - Canavan, Kim N (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
South African riparian zones have been heavily degraded through anthropogenic activities such as dam construction and extraction of water for irrigation, which has resulted in a loss of ecosystem services and functioning. A consequence of such disturbances to riparian areas is in their susceptibility to invasive alien species (IAS). One such IAS is the giant reed, Arundo donax L. (Poaceae), introduced to South Africa in the 1700s largely for erosion control. Arundo donax has since greatly expanded in the country and is now one of the most abundant IAS. Arundo donax has been found to displace native vegetation and in South Africa this will most likely lead to the displacement of the native tall-statured grasses, Phragmites australis (Cav.) Trin. ex Steud. and Phragmites mauritianus Kunth. This study aimed to enhance our understanding of the tall-statured grasses A. donax, P. australis and P. mauritianus to better manage them in riparian areas. For A. donax, biological control is seen as the most viable option to control stands in the long-term. However, before such a programme is put in place, it is important to first collect baseline data that can be used to guide the direction of the biological control project in South Africa. For the Phragmites spp., despite being a dominant vegetative type in riparian areas, very little is known about their status in South Africa. Furthermore, there have been increasing reports of both Phragmites species having an expansion of their range and abundance. In North America, there has been a similar trend of reed expansion and through molecular work it was determined that a cryptic invasion has occurred with the introduction of an invasive non-native haplotype from Europe. It is therefore unknown if Phragmites spp. populations are expanding due to anthropogenic activities or due to a cryptic invasion. To address these shortfalls in knowledge the study investigated the tall-statured grasses in two parts; firstly, molecular techniques are used to explore the plant origin and genetic diversity of A. donax, P. australis and P. mauritianus and secondly using the Enemy Release Hypothesis as a framework, herbivore assemblages for each reed was determined across their distribution in South Africa. Molecular-techniques determined that both P. australis and P. mauritianus had only one haplotype - known as haplotype K and haplotype V respectively, across their distribution. For P. australis, haplotype K shares a close connection with populations from a Mediterranean lineage and this was further confirmed with a shared grass-waxy band. The direction and timing of genetic exchange between the two regions could not be ascertained and thus still remains unknown. Microsatellite analysis determined that both Phragmites spp. had a high genetic diversity compared to worldwide lineages. With no evidence of any cryptic invasions of haplotypes from other regions, both Phragmites spp. populations are likely to be native to South Africa. For A. donax all populations across South Africa were determined to be haplotype M1; a cosmopolitan haplotype that has an ancient native range in Afghanistan and Pakistan (Indus Valley). Populations were found to have no genetic diversity and thus can be considered one clone. A pre-introductory survey determined a list of herbivores associated with each tall- statured grass. For A. donax, a total of seven herbivores were found. Of these, one herbivore, a galling wasp, Tetramesa romana Walker (Hymenoptera: Eurytomidae) was found to be highly abundant and widely distributed in South Africa. Tetramesa romana is already a biological control agent in North America and thus is likely exerting some pressure on A. donax populations in South Africa. For both Phragmites spp. a total of ten herbivores were found, although having higher species richness compared to A. donax, when compared to other regions, these native species have a relatively low species richness. Providing baseline data on plant origin, genetic diversity and herbivory on A. donax, P. australis and P. mauritianus has provided important information on managing these species in riparian ecosystems in South Africa. For the Phragmites spp. with no evidence of any cryptic invasions, it is recommended that reed stands continue to be managed as native species. Phragmites spp. are important dominant vegetative species and thus should be protected; however, if reed stands become expansive, control methods can be put in place to focus on managing spread and abundance. For A. donax, this study was able to provide pivotal information in guiding the biological control programme. By determining the ancient lineage of South African populations, research can be focused in this area to find potential biological control agents. Lastly, the pre-introductory survey determined that a biological control agent, T. romana was already established with an unknown introduction and also highlighted potential plant parts that should be targeted. In particular, no rhizome feeding herbivores were found in South Africa and therefore this highlights an important niche that should be explored in biological control agents.
Keywords: Insects as biological pest control agents -- South Africa; Arundo donax; Giant reed -- South Africa; Giant reed -- Biological control -- South Africa; Phragmites australis; Phragmites mauritianus; Phragmites; Tetramesa romana; Biological invasions -- South Africa; Wasps -- Host plants; Wasps -- South Africa